DAIRY FARMERS’ KNOWLEDGE AND STANDPOINTS REGARDING FORAGE PRESERVATION TECHNOLOGY IN “NEW NORMAL” ADAPTATION (A Case Study in Pujon District) - Fibriyanti, Dian; Tain, Anas Tain; Bakhtiar, Ary; Kombe, Luinasia Elikunda (Jurnal AGRISEP, 2022)
Covid-19 pandemic has restricted social and physical mobility, such as using a mask during outdoor activities, applying hand sanitizer, washing hands, and maintaining health by exercising and controlling body intake. These restrictions also have caused the termination of forage subsidy by the milk processing industries. The “new normal” era requires farmers to secure self-sufficient forage. This research aims to 1; analyze the characteristic situation of the respondents regarding forage preservation technology in “new normal” adaptation, 2; analyze the insight and standpoints of the dairy farmers regarding forage preservation technology in “new normal” adaptation. The researchers used the descriptive analysis method and obtained 50 respondents by purposive sampling in Pujon District. The results showed that 63.70% of the respondents are “moderately informed," and 61.45% have "moderate standpoints". In conclusion, so it was concluded that the level of knowledge about forage feed preservation technology affected the attitude of farmers in applying forage feed preservation technology. the forage preservation technology is well-established and applicable among the dairy farmers in Pujon District.